Prognostic Significance of Pre-treatment Serum Inflammatory Biomarkers on Survival in Patients with Carcinoma Cervix Treated by Radical Radiotherapy or Chemo-radiation - Nair, Lekha Madhavan; Babu, Aneesha; M, Jagathnath Krishna K; Kumar, Aswin; Mathews, Susan; Joseph, John; James, Francis Vadakkumparambil (Asian Pacific Journal of Cancer Care, 2021)
Background: Inflammation has an important role in the initiation and progression of carcinoma cervix. The measurement of inflammatory biomarkers is a cost-effective method of identifying patients at high risk of recurrence after treatment. This study was done to identify the influence of pre-treatment inflammatory biomarkers on survival in patients treated with radical chemo-radiation or radiation. Methods: Patients with biopsy proven carcinoma cervix treated with Radiotherapy or Chemo-radiation from January 1st, 2016 to September 30th, 2017 were included. Pre-treatment complete blood counts, differential counts, serum albumin and C-reactive protein (CRP) were obtained. Neutrophil lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR) and CRP Albumin ratio (CAR) were calculated. The best cut off values for NLR, PLR, serum albumin, CRP and CAR were found out from receiver operating characteristic (ROC) curves. OS (Overall Survival) and DFS (Disease Free Survival) were estimated using Kaplan -Meier method. The prognostic value of inflammatory biomarkers on survival was assessed by cox regression model. Results: Sixty-three patients were included. The median follow up was 42.5 months. The best cut off values for NLR, PLR, albumin, CRP and CAR from the ROC curve were 2.36, 122.725, 3.95, 0.65 and 0.8 respectively. The three-year OS and DFS probability were 68.3% and 63.5% respectively. Patients with CAR >0.8 had 5.7 times more risk of death and 6.01 times risk of relapse or progression compared to patients with CAR ≤0.8. Conclusion: Patients with a CRP-Albumin ratio of more than 0.8 are at significant risk of relapse and death after chemoradiation or radiation.